Cyclophilin PpiB is involved in motility and biofilm formation via its functional association with certain proteins. (16th June 2016) - Skagia, Aggeliki; Zografou, Chrysoula; Vezyri, Eleni; Venieraki, Anastasia; Katinakis, Panagiotis; Dimou, Maria
Abstract : PpiB belongs to the superfamily of peptidyl‐prolyl cis / trans isomerases (PPIases, EC: 5.2.1.8), which catalyze the rate‐limiting protein folding step at peptidyl‐prolyl bonds and control several biological processes. In this study, we show that PpiB acts as a negative effector of motility and biofilm formation ability of Escherichia coli . We identify multicopy suppressors of each Δ ppiB phenotype among putative PpiB prey proteins which upon deletion are often characterized by analogous phenotypes. Many putative preys show similar gene expression in wild‐type and Δ ppiB genetic backgrounds implying possible post‐translational modifications by PpiB. We further conducted in vivo and in vitro interaction screens to determine which of them represent true preys. For DnaK, acetyl‐CoA carboxylase, biotin carboxylase subunit (AccC) and phosphate acetyltransferase (Pta) we also showed a direct role of PpiB in the functional control of these proteins because it increased the measured enzyme activity of each protein and further interfered with DnaK localization and the correct folding of AccC. Taken together, these results indicate that PpiB is involved in diverse regulatory mechanisms to negatively modulate motility and biofilm formation via its functional association with certain protein substrates. Abstract : Cyclophilin PpiB negatively modulates swimming, swarming motility and biofilm formation ability of Escherichia coli . Many multicopy suppressors of each phenotype interact with PpiB, and in some cases, PpiB is able to functionally control these proteins.